Controlled growth and spectroscopy characterization of blue violet perovskite quantum dots in borate glasses. Issue 12 (15th June 2023) - Lin, Mengqi; Zhang, Xizhen; Dong, Yabo; Xu, Sai; Li, Xiangping; Yu, Hongquan; Sun, Jiashi; Cheng, Lihong; Chen, Baojiu
Abstract: Blue violet light emitting CsPb(Cl/Br)3 perovskite quantum dots glasses (QDGs) have been successfully fabricated in multi-component borate glass matrix by melt quenching and heat treatment. The spectral characteristics have been evaluated by photoluminescence (PL), PL excitation (PLE), PL decay and absorption spectra. The recipe and preparation conditions have been optimized for controlled growth of QDs. By using raw materials of NH4 Br/NH4 Cl/PbO and crucible cover, optimizing composition of Na2 O/K2 O in matrix, melting temperature and time, heat treatment temperature and time, and NH4 Cl and NH4 Br contents, we have finally realized blue violet exciton emission in target range of 405–440 nm. The PL wavelength adjustment is comprehensive effect of the abovementioned influence factors. The emission in short wavelength of 405–440 nm is due to controlled growth of the QDs. In final CsPb(Cl/Br)3 QDs, the contents of Cl and Br are suitable and the Cl/Br ratios are large. A little Br is necessary for growth of CsPb(Cl/Br)3 QDs and then the Br is partially replaced by Cl at suitable treatment condition. Unsymmetrical PL spectrum profile of some samples is explained as reabsorption effect by monitoring PL spectral profile and PL decay. The temperature characteristics of PL spectra show good recoverability after a temperature cycle.